The Analgesic Effect of Ethanol Extract Soursop (Annona muricata L.) Leaves in Wistar Rats - Kuswinarti Kuswinarti; Kendry Savira; Reno Rudiman (Althea Medical Journal, 2018)
Background: Pain is an emotional and sensory experience that is unpleasant and related to tissues damage. In the past, Soursop (Annona muricata L.) leaves have been believed to be able to relieve pain. This study aimed to explore the analgesic effect of soursop leaves and its effective dose in an animal model. Methods: Wistar rats (n=25) had been used in this experimental study, divided into 5 groups; consisting of a negative control group, experiment groups using extract soursop leaves with doses of 200mg/kgbw, 400 mg/kgbw and 600 mg/kgbw, and natrium diclofenac as a positive control. One hour after treatment, all groups of rats were induced by carrageenan-lambda in the feet. The basal retraction of rats’ legs was measured in 47oC water and repeated at two, four, and six hours. The data were analyzed using analysis of variance and Tukey’s test. Result: The dose of 200 mg/kgbw had no analgesic effect (p>0.05), while the dose of 600 mg/kgbw had the highest analgesic effect at 7.72 seconds on the 4th hour of induction. On the 6th hour, the dose of 400 mg/kgbw had the highest analgesic effect at 3.58 seconds.Conclusions: Extract soursop (Annona muricata L.) leaves in this study have been proven to have an analgesic effect.